Advancing health equity in cancer care: The lived experiences of poverty and access to lung cancer screening - Sayani, Ambreen; Vahabi, Mandana; O’Brien, Mary Ann; Liu, Geoffrey; Hwang, Stephen; Selby, Peter; Nicholson, Erika; Giuliani, Meredith; Eng, Lawson; Lofters, Aisha (PLOS ONE, 2021)
Background Individuals living with low income are more likely to smoke, have a higher risk of lung cancer, and are less likely to participate in preventative healthcare (i.e., low-dose computed tomography (LDCT) for lung cancer screening), leading to equity concerns. To inform the delivery of an organized pilot lung cancer screening program in Ontario, we sought to contextualize the lived experiences of poverty and the choice to participate in lung cancer screening. Methods At three Toronto academic primary-care clinics, high-risk screen-eligible patients who chose or declined LDCT screening were consented; sociodemographic data was collected. Qualitative interviews were conducted. Theoretical thematic analysis was used to organize, describe and interpret the data using the morphogenetic approach as a guiding theoretical lens. Results Eight participants chose to undergo screening; ten did not. From interviews, we identified three themes: Pathways of disadvantage (social trajectories of events that influence lung-cancer risk and health-seeking behaviour), lung-cancer risk and early detection (upstream factors that shape smoking behaviour and lung-cancer screening choices), and safe spaces of care (care that is free of bias, conflict, criticism, or potentially threatening actions, ideas or conversations). We illuminate how ‘choice’ is contextual to the availability of material resources such as income and housing, and how ‘choice’ is influenced by having access to spaces of care that are free of judgement and personal bias. Conclusion Underserved populations will require multiprong interventions that work at the individual, system and structural level to reduce inequities in lung-cancer risk and access to healthcare services such as cancer screening.